Eschatology Study According to the Book of Daniel 12:1-2 on the Resurrection of the Dead and the Great Tribulation and Its Application to Believers in the Second Coming of Christ - Dewanto, Yogi (ARRUS Journal of Social Sciences and Humanities, 2025)
Daniel 12:1-2 contains important prophecies concerning the resurrection of the dead and the great tribulation at the end of the age. A proper understanding of this passage contributes significantly to the development of eschatological doctrine in both Jewish and Christian traditions. This study aims to examine the theological concepts of resurrection and the great tribulation in Daniel 12:1-2 and to evaluate their practical application for believers preparing for the second coming of Christ. The research method used is a qualitative approach, utilizing biblical textual analysis, a theological literature review, and interviews with respondents from the Christian community. The results found that Daniel 12:1-2 presents a strong eschatological framework concerning the separation of the righteous from the wicked through the resurrection, while also warning of the coming of the great tribulation as a marker of the end times. The Book of Daniel provides a fundamental foundation for eschatological theology. Reflection on Daniel 12:1-2 encourages believers to pursue spiritual readiness, live in holiness, and strengthen their hope for the second coming of Christ.